A cross-sectional study on health behavior changes during COVID-19 among adults in Malaysia - Ithnain, Norbaidurah; Kassim, Rosnani; Amirudin, Nadia; Aimanan, Siti Nurhanim Mohamed; Krishnan, Manimaran; Panting, Albeny Joslyn (Frontiers in Public Health, 2024)
IntroductionCOVID-19 has triggered significant disruptions globally, necessitating swift adaptations in individuals’ health behaviors.MethodsThis cross-sectional study was conducted during Phase Four of Malaysia’s National Recovery Plan and examines how the pandemic has affected health behaviors among adult Malaysians. The study gathered data online using convenience sampling with 1,004 respondents aged 18 and above. The research focused on diverse health domains, including eating habits, physical activity, smoking, alcohol consumption, and sleep patterns. The Wilcoxon Signed Rank test and descriptive statistics were employed to compare health behaviors before and after COVID-19.ResultsFindings indicate noteworthy shifts in eating behaviors, with increased water and fruit consumption (p < .001). The frequency of home-cooked meals stayed relatively stable despite declining dinner preference and increasing daily snacks. Physical activity declined, marked by increased sedentary behavior and screen time (p < .001). There were differences in the patterns of smoking and alcohol consumption; some had started these behaviors during the pandemic. Notably, intentions to quit smoking among respondents were more prominent than attempts to stop drinking. Respondents’ sleep patterns also changed, with more sleeping fewer than seven hours daily (p < .001).ConclusionThe study emphasizes the need for focused interventions to address new challenges by highlighting the impact on health behaviors. As Malaysia navigates the post-pandemic landscape, understanding and mitigating the persisting effects on health behaviors are crucial for promoting overall well-being.